Effects of Team-Assisted Instructions on Motivation of Vocational High School Students in Physical Education (Universitas Pendidikan Indonesia, 2024)
In physical education (PE), the lack of motivation becomes a problem in the learning process, leading to the student inactivity and late in participating in physical education lessons. Therefore, it is necessary to use appropriate learning models to increase the student motivation in learning physical education. The learning model that can be used to improve the student motivation is the Team-Assisted Instructions (TAI) as one of the Cooperative Learning (CL) model types. This research aimed to examine the effect of TAI on the motivation of vocational high school students in learning physical education. The research method used experimental research with one-group pretest-posttest design. The participants involved in this study were 25 class X students from one of the vocational high schools in Indramayu Regency selected using the saturated sampling technique. The instrument used in this research was the Academic Self-Regulation Questionnaire in physical education learning for middle and high school students. The data analysis technique of this research employed statistical descriptions and paired sample t-tests. The research results indicate that there is an effect of TAI on the motivation of vocational high school students in learning physical education. Further research is suggested to conduct investigations regarding the TAI model fidelity and the use of references in the implementation of TAI.